Cutting through the noise : the right employee engagement strategies for you - Dávila, Norma (ASTD Press, 2013)
Managers are flooded with theories, concepts, and ideas for how to improve employee engagement, but what works, and what doesn't? This book helps managers cut through the clutter of all those strategies and find the one that works for them. Beginning with the myths and realities of employee engagement, authors Dv̀ila and Pią-Ramr̕ez highlight the importance of organizational culture and context when it comes to keeping employees invested in the organization. You will understand the various stages of employee engagement; consider change management as a critical issue in employee engagement; learn how to maintain that engagement throughout your employees' careers. --